Estimation of DWDM Transmission for Broadband Access with FBG Technology - Ozolins, O.; Ivanovs, G. (Elektronika ir Elektrotechnika, 2011)
In this paper authors have measured amplitude transfer functions of FBG technology optical filters with 50 GHz and 100 GHz FWHM bandwidth and have evaluated their performance in 2.5 Gbit/s and 10 Gbit/s DWDM transmission system over a typical length of broadband access network. Reliable transmission is realized for eight channels 2.5 Gbit/s DWDM transmission system with 50 GHz FBG for 20 km of SSMF and for eight channels 10 Gbit/s DWDM transmission system with 50 GHz FBG for reduced distance (10 km of SSMF). Ill. 6, bibl. 10 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.111.5.346